2020
DOI: 10.1161/circep.119.007437
|View full text |Cite
|
Sign up to set email alerts
|

Major Adverse Cardiovascular Events Associated With Postoperative Atrial Fibrillation After Noncardiac Surgery

Abstract: Background: Postoperative atrial fibrillation (POAF) is a frequent occurrence after noncardiac surgery. It remains unclear whether POAF is associated with an increased risk of major adverse events. We aimed to elucidate the risk of stroke, myocardial infarction, and death associated with POAF following noncardiac surgery by a meta-analysis of randomized controlled studies and observational studies. Methods: We searched electronic databases from inceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 59 publications
0
41
0
1
Order By: Relevance
“…39 Patients who develop POAF after noncardiac surgery are at an increased risk for stroke, death, and other cardiovascular events at 1 year after surgery. [40][41][42][43] A post hoc analysis combined data from the PeriOperative ISchemic Evaluation POISE-1 44 and POISE-2 trials 45,46 and included 18,117 patients (mean age 69 years, 57.4% male) with, or at risk of, cardiovascular disease who were undergoing noncardiac surgery and were not in AF at the time of study enrollment. Compared to those without POAF, patients with POAF had a higher incidence of stroke 1 year after surgery (5.58 vs. 1.54 per 100 patient years; aHR = 3.43; 95% CI: 2.00-5.90).…”
Section: What Is the Clinical Relevance Of Poaf?mentioning
confidence: 99%
“…39 Patients who develop POAF after noncardiac surgery are at an increased risk for stroke, death, and other cardiovascular events at 1 year after surgery. [40][41][42][43] A post hoc analysis combined data from the PeriOperative ISchemic Evaluation POISE-1 44 and POISE-2 trials 45,46 and included 18,117 patients (mean age 69 years, 57.4% male) with, or at risk of, cardiovascular disease who were undergoing noncardiac surgery and were not in AF at the time of study enrollment. Compared to those without POAF, patients with POAF had a higher incidence of stroke 1 year after surgery (5.58 vs. 1.54 per 100 patient years; aHR = 3.43; 95% CI: 2.00-5.90).…”
Section: What Is the Clinical Relevance Of Poaf?mentioning
confidence: 99%
“…It is also more common in the elderly and patients with underlying atherosclerotic cardiovascular disease and is associated with an increased risk of stroke and death within 30 days after surgery. 13 New-onset atrial fi brillation was previously thought to be transient and benign; however, recent systematic reviews and meta-analyses reported an increased long-term risk for atrial fi brillation recurrence as well as for cardiovascular and cerebrovascular events. 13,15 Although most patients with postoperative atrial fi brillation persisting more than 48 hours tend to receive anticoagulation, it is unclear whether they or patients with transient postoperative atrial fi brillation require anticoagulation or for what duration.…”
Section: ■ Anticoagulation For Postoperative Atrial Fibrillationmentioning
confidence: 99%
“…13 New-onset atrial fi brillation was previously thought to be transient and benign; however, recent systematic reviews and meta-analyses reported an increased long-term risk for atrial fi brillation recurrence as well as for cardiovascular and cerebrovascular events. 13,15 Although most patients with postoperative atrial fi brillation persisting more than 48 hours tend to receive anticoagulation, it is unclear whether they or patients with transient postoperative atrial fi brillation require anticoagulation or for what duration. 14,15 Unknown is the long-term risk of cerebrovascular events in these patients and whether they should be treated similarly to patients with chronic nonvalvular atrial fibrillation, as the benefi t of preventing thromboembolism must be balanced against the risk of bleeding with anticoagulation.…”
Section: ■ Anticoagulation For Postoperative Atrial Fibrillationmentioning
confidence: 99%
“…Discussion: These results show that rib fixation carries a significant risk for perioperative cardiac dysrhythmia. Historical controls show the incidence of arrhythmia in non-cardiac, thoracic surgery to be between 17-30%, with atrial fibrillation accounting for the majority [2,3,4,5]. The total incidence of any arrhythmia after rib plating was 73%, which is significantly higher than the upper boundary (30%) of historical norms (p = 0.0003) [Table 2].…”
Section: Referencesmentioning
confidence: 99%